Panoramic View of Boosters to Convention of California Development Board
Group photo at unknown train station Witten on photo: Boosters to Convention of Calif. Development Board January 12-13, 1912, Photo by Panama Pacific Photo and Art Co. P.O. Box 1166 Los Angeles, Cal.